Investigation of biological activity of nickel (II) complex with naproxen and 1, 10-phenanthroline ligands. Issue 18 (12th December 2021) - Mirzaei-Kalar, Zeinab; Khandar, Ali Akbar; White, Jonathan M.; Abolhasani, Hoda; Komeili Movahhed, Tahereh; Best, Stephen P.; Jouyban, Abolghasem
Abstract: After the accidental discovery of cis-platinum, extensive attempts have centralized on the rational design of metallic compounds for cancer treatment. Here a solvent-dependent complex of nickel (II) with 1, 10-phenanthroline and naproxen, [Ni(1, 10-phenanthroline)(naproxen)2 (solvent)], solvent = 83% H2 O and 17% EtOH in the crystal structure, has been synthesized and specified by the X-ray structure analysis. It's in vitro DNA binding was inspected by the multispectroscopic methods and gel electrophoresis. The data of DNA-viscosity and competition fluorimetric test by methylene blue (MB) and Hoechst 33258 confirm groove binding mode of the complex to CT-DNA. Comparison of the results of this binding study with previous work revealed that the mode of binding of small compounds to DNA is highly influenced by the structure of the compounds. The DNA cleavage potency of the complex was appraised by the agarose gel electrophoretic and it was found that the complex does not have any momentous cleavage potency on the pUC18 plasmid DNA. The cytotoxicity of the complex on HT 29, HepG2 and HEK-293 cell lines by MTT method indicates that %inhibition of the complex on HT 29 is better than HepG2, compared with cisplatin drug. On HEK-293 cells, %inhibition growth of normal cells of the complex is less than cisplatin. Flow cytometry analysis of the complex on the HT 29 cells indicated the apoptosis cell death. RT-PCR studies revealed down-regulation of BCL2 expression, while the expression of BAX, caspase 3 and BAX/BCL2 genes was up-regulated in HT 29 cells by the complex. Highlights: A solvent-dependent nickel (II) with naproxen and 1, 10-phenanthroline with aqueous solubility was synthesized and characterized. All experimental results indicate a groove mode of binding of the complex to CT-DNA. Potential biological characteristics confirmed that the complex is a promising candidate as anticancer agent. Communicated by Ramaswamy H. Sarma